Zinc-Induced Effects on Productivity, Zinc Use Efficiency, and Grain Biofortification of Bread Wheat under Different Tillage Permutations - Usman Zulfiqar (Agronomy, 2020)
Zinc (Zn) deficiency is a global concern for human health and causes a decrease in crop production and nutritional characteristics. A two-year field study was planned to evaluate comparative effects of various Zn application approaches in bread wheat under plough tillage (PT) and zero tillage (ZT) system. Cultivation of wheat under ZT improved the soil organic carbon (17%), total soil porosity (11%), soil microbial biomass nitrogen (5%), and carbon (5%) in comparison to PT system averaged across the two years. Various efficiency indices were significantly influenced by Zn application methods during both years of experimentation. However, grain Zn contents were maximum with foliar-applied Zn in PT (31%) and soil-applied Zn under the ZT system (29.85%). Moreover, Zn use also enhanced the bioavailable Zn as lower phytate contents and phytate to Zn molar ratio were recorded. The highest bioavailable Zn was calculated for foliar (30%) and soil application (28%). Under both tillage systems, the maximum net benefits were obtained through Zn seed priming; nevertheless, ZT resulted in higher net benefits than PT due to low associated costs. In conclusion, Zn nutrition through different methods enhanced the productivity, profitability, and grain biofortification of wheat under PT and ZT systems.